2010
DOI: 10.1177/1096348010370867
|View full text |Cite
|
Sign up to set email alerts
|

Career Decision Making and Intention: a Study of Hospitality Undergraduate Students

Abstract: This study determined factors influencing undergraduate hospitality students’ career intentions in the hospitality industry. A total of 360 hospitality students completed a survey that assessed career decision making, expected outcomes, and items focused on academic-related decisions and demographic background. Logistic regression analysis revealed that career intentions in hospitality were significantly associated with students’ gender, work experience, transfer status, and outcome expectations in the industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 39 publications
5
91
0
Order By: Relevance
“…These findings largely reflect highlighting perceived lack of available jobs in enhancing the attraction towards educational options (Furlong and Cartmel 2007), and provide evidence for the notion of higher education attendance as being motivated by the prospect of enhancing career or employment opportunities. This somewhat reflects previous work which indicates the role of outcome expectancies as key factors associated with career intentions (Chuang and Dellmann-Jenkins 2010). This notion was particularly noteworthy in Focus Group 3, highlighted in Extract 8, in discussions about considering employment in the context of the current labour market.…”
Section: Pre and Post Fee Risesupporting
confidence: 80%
“…These findings largely reflect highlighting perceived lack of available jobs in enhancing the attraction towards educational options (Furlong and Cartmel 2007), and provide evidence for the notion of higher education attendance as being motivated by the prospect of enhancing career or employment opportunities. This somewhat reflects previous work which indicates the role of outcome expectancies as key factors associated with career intentions (Chuang and Dellmann-Jenkins 2010). This notion was particularly noteworthy in Focus Group 3, highlighted in Extract 8, in discussions about considering employment in the context of the current labour market.…”
Section: Pre and Post Fee Risesupporting
confidence: 80%
“…Similar to studies done by Skorikov [10] that studied factors affecting career preparation behavior, career decision-making is a leading variable of behavior occupational exploration. Chuang and Dellmann-Jenkins [11] supported the relationship between career decision-making and occupational exploration with the result that student who have a high career decision-making also have high occupational exploration.…”
Section: Hypothesismentioning
confidence: 97%
“…In a study on gender and workrelated attributes among seniors graduating from a hospitality program in the USA, Vest and Murrmann (1992) found that, compared to males, females placed a stronger emphasis on growth (career, job security, and training); control (job content, control over own work); and constraints (time and place, relocation, work schedule). A study by Chuang and Dellmann-Jenkins (2010) on undergraduate hospitality students' career intentions in the hospitality industry showed that gender and work experience were associated with career intentions in the industry, with females having stronger career intentions than males. The hotel and restaurant industry is a gendered labor market in Norway.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%